The Samaritans in the New Testament - Sloyan, Gerard Stephen (Horizons, 1983)
In a painful paradox the word "good" has become forever attached to "Samaritan" by Jesus' Lucan parable (Lk 10:29-37; see 17:16), even while bitter Jewish hostility to this group has continued over the centuries: through the highly redacted polemic against the Samaritans of 2 Kgs 17 (see Sir 50:26) and through Talmudic commentary on it such as that in bKiddushin 75. Dan Jacobson in his recent The Story of the Stories: The Chosen People and Its God sees a "propagandistic … intention" in the parable of the Good Samaritan:It is significant that the passerby who succors the injured man is a Samaritan—i.e., not a Jew, let alone of the priests or levites. ("For Jews have no dealings with the Samaritans," says the fourth chapter of John, describing a meeting between Jesus and yet another strikingly well-disposed Samaritan.)In the first century, as now, the praise accorded this separated Jewish group in the Christian writings must have rankled those Judean, Galilean and diaspora Jews to whose notice it came. It would have confirmed them in their view of the noṣrim as incorrigibly deviant from halakah. The principle of the ancient world was, "Your friends are my friends and your enemies are my enemies." The favorable notice given to these enemies of the Jews by Jesus' followers could only have set the movement back in Jewish eyes.